THE EFFORTS TO IMPROVE TEACHERS’ ACHIEVEMENT MOTIVATION IN ACHIEVING NATIONAL EDUCATION GOAL - Eripuddin; Hardianto (English Study Program University of Pasir Pengaraian, 2018)
JEE (Journal of English Education) is a scientific journal that collects the results of the research and scientific work of lecturers, teachers, or students associated with learning and teaching English. It is a blind peer review international journal which publishes manuscripts within the fields of Teaching English as a Foreign Language (TEFL), Teaching English to Speakers of Other Languages (TESOL), English for Specific Purposes (ESP), Applied Linguistics, Literature and English Teaching, Discourse Analysis, Culture and Language (more on focus and scope). It is published by English study program of University of Pasir Pengaraian, Riau, Indonesia. It is published twice a year in June and December (P-ISSN: 2459-9719 E-ISSN: 2597-7091).